MEMBANGUN KEPERCAYAAN DAN KETERLIBATAN: PEMANFAATAN VLOG OLEH TOKOH PUBLIK PEMERINTAHAN - Shiddiq Sugiono; Irwansyah Irwansyah (Jurnal Media dan Komunikasi (MEKAS), 2023)
This research explores the role and impact of the use of vlogs (video blogs) by government public figures in an effort to build trust and community engagement. In the digital era, communication between the government and citizens undergoes a significant transformation, with the use of digital platforms as an effective means of communication. Vlogs have become one of the popular forms of communication among public figures, allowing them to interact directly with citizens and share informative and personal content. Keywords: vlog, storytelling, public figure, digital media, audio visual. This study uses qualitative analysis methods by analyzing various vlogs uploaded by government public figures, such as government officials, legislators, and regional leaders, in various contexts. We also conducted interviews with a number of respondents who followed the vlog to understand their perceptions of trust and engagement built through the vlog. The results of this study show that the use of vlogs by government public figures has great potential in building public trust and involvement. Vlogs provide opportunities for public figures to communicate government information, convey aspirations, and establish emotional connections with citizens. Success in building trust and engagement through vlogs also depends on content factors, transparency, and active engagement with the online community. This research provides valuable insights into the role of vlogs in government communication in the digital age and their contribution to the formation of a positive image of public figures. The implications of this research can help government stakeholders in designing more effective communication strategies to build trust and community engagement in the digital age.